Is adherence to the 24-hour movement guidelines associated with a reduced risk of adiposity among children and adolescents? - Lukáš Jakubec; Aleš Gába; Jan Dygrýn; Lukáš Rubín; Adam Šimůnek; Erik Sigmund (BMC, 2020)
Abstract Background Little is known about the combined effect of physical activity (PA), recreational screen time (ST), and sleep in preventing childhood obesity. Hence, this study aimed to analyze the associations between meeting the PA, ST, and sleep recommendations within the 24-hour movement guidelines and adiposity indicators among children and adolescents. Methods A total of 679 children and adolescents aged 8-18 years were included. The time spent in moderate-to-vigorous PA and the sleep duration were estimated from raw data from a wrist-worn accelerometer. Recreational ST was reported by the child or parent. Body mass index (BMI) z-score, fat mass percentage (FM%), and visceral adipose tissue (VAT) were used as adiposity indicators. Participants with ≥ 60 min/day of moderate-to-vigorous PA, < 2 h/day of recreational ST, and uninterrupted sleep for 9-11 h/day (for children) or 8-10 h/day (for adolescents) were considered to meet the overall 24-hour movement guidelines. Results Meeting the ST only recommendation was associated with reduced odds of a high BMI z-score (odds ratio [OR] = 0.38, 95% confidence interval [CI]: 0.17-0.89), excess FM% (OR = 0.34, 95% CI: 0.13-0.93), and excess VAT (OR = 0.27, 95% CI: 0.10-0.74) in adolescents. Significantly reduced odds of a high BMI z-score was associated with meeting the combination of the ST and sleep recommendations (OR = 0.11, 95% CI: 0.01-0.89). Adolescents who met one recommendation (OR = 0.51, 95% CI: 0.27-0.96) or any two recommendations (OR = 0.33, 95% CI: 0.11-0.94) had reduced ORs of having a high BMI z-score. Adolescents had lower odds of having excess VAT if they met one recommendation (OR = 0.39, 95% CI: 0.19-0.81) or any two recommendations (OR = 0.25, 95% CI: 0.07-0.90). No significant associations were found in children. Conclusions The present study showed no associations between meeting all three recommendations within the 24-hour movement guidelines and adiposity indicators. However, meeting ST only recommendation and the combination of the ST and sleep recommendations was associated with a reduced risk of excess adiposity. This finding should be considered when designing effective strategies and interventions to prevent childhood obesity.